Unified calculation formula for predicting the shear stresses in prismatic and non-prismatic beams with corrugated steel webs. (February 2021) - Zhou, Man; Liao, Jiacong; Zhong, Jitao; An, Lin; Wang, Haibo
Abstract: The existing shear design theories for hybrid beams with corrugated steel webs (CSWs) used in China and Japan were originally proposed for only prismatic hybrid beams with CSWs. The traditional calculation method assumes that the bending stiffness and axial stiffness of a beam with CSWs are provided by the top and bottom concrete flanges, while the shear stiffness is contributed entirely by the CSWs. However, due to the influence of the Resal effect on a non-prismatic hybrid beam with CSWs, the calculated shear stress of the CSWs will be overpredicted if the shear capacities of the top and bottom concrete flanges are ignored (especially for the case of an inclined bottom flange). These traditional assumptions may no longer be applicable to non-prismatic structural members. Considering the Resal effect and accordion effect of non-prismatic beams with CSWs, this study proposed a practical unified calculation formula suitable for calculating the shear stresses of prismatic and non-prismatic hybrid beams with CSWs. The accuracy and adaptability of this unified calculation formula were verified through prismatic and non-prismatic beam model tests as well as finite element simulations. Moreover, the authors quantitatively discussed the calculation errors of the traditional calculation assumptions for non-prismatic beams with CSWs. In addition, a finite element parameter analysis was performed on a non-prismatic beam with CSWs near the support to clarify the applicable conditions of the unified calculation formula. The numerical results show that when the inclination angle of the bottom flange varies within the range of 0° to 20°, the calculation error of the proposed unified calculation formula is controlled to within 15%, exhibiting good adaptability to changes in the inclination angle. The unified calculation formula can still predict the shear stresses in tapered CSWs with an error of less than 20% when the sum of the thicknesses of the top and bottom concrete flanges does not exceed 20% of the total beam height. It is expected that this study can further develop the shear stress calculation theory for non-prismatic beams with CSWs, thus providing a reference for the reasonable design of tapered CSWs.